Chinese Foreign Direct Investment in MERCOSUR: : How does it converge with the Belt and Road Initiative objectives? - Munhoz da Rocha Caporali, Henrique; Carta Winter, Luís Alexandre (Revista de Direito Internacional e Globalização Econômica, 2024)
As one of the largest world economies, China maintains close political and economic ties with its commercial partners. The country aims to strengthen those links through Foreign Direct Investment (FDI), referring to the Belt and Road Initiative (BRI) in infrastructure projects. This initiative seeks to help develop the participating countries’ infrastructure, provide ways to solve the excess capacity faced in some industry sectors in China, promote the renminbi’s internationalization, and tighten the already existing ties. Within this context, one must consider the context of the MERCOSUR countries, which have a long-standing relationship with China regarding commercial flows and political convergence. Therefore, this paper assesses whether Chinese FDI in MERCOSUR countries converges with the stated BRI objectives. Through the deductive method, it concludes that in the three main sectors benefited by Chinese FDI in each MERCOSUR country, regardless of formal ties to the BRI, there is an evident focus on Energy, Transportation, and Metal fields, which not only converge with the above-stated objectives but also provide China with essential commodities to fuel their high-tech industry.